2017
DOI: 10.1152/jn.00964.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human subthalamic neuron phase-locking to motor and sensory cortical oscillations during movement

Abstract: Coupled oscillatory activity recorded between sensorimotor regions of the basal ganglia-thalamocortical loop is thought to reflect information transfer relevant to movement. A neuronal firing-rate model of basal ganglia-thalamocortical circuitry, however, has dominated thinking about basal ganglia function for the past three decades, without knowledge of the relationship between basal ganglia single neuron firing and cortical population activity during movement itself. We recorded activity from 34 subthalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 56 publications
9
36
0
Order By: Relevance
“…A smaller proportion (15%) of decrease-type responses were locked to speech production onset, with remaining responses not clearly associated with either event. Altought minority populations of neurons with movement-related firing-rate decreases have been reported previously (Wichmann et al, 1994;Schrock et al, 2009;Lipski et al, 2017), and active movements have been associated with a higher proportion of decrease-type responses in the STN (Lipski et al, 2017), it is remarkable that such a high percentage of decrease-type responses were observed in the present study. Interestingly, and in contrast to our results, a marked reduction of STN activity was reported to be associated with the onset of speech production in the only previous report of STN unit activity recorded during speech production (Watson and Montgomery, 2006), although that study was largely descriptive in nature, limiting comparisons to our data.…”
Section: Discussionsupporting
confidence: 65%
“…A smaller proportion (15%) of decrease-type responses were locked to speech production onset, with remaining responses not clearly associated with either event. Altought minority populations of neurons with movement-related firing-rate decreases have been reported previously (Wichmann et al, 1994;Schrock et al, 2009;Lipski et al, 2017), and active movements have been associated with a higher proportion of decrease-type responses in the STN (Lipski et al, 2017), it is remarkable that such a high percentage of decrease-type responses were observed in the present study. Interestingly, and in contrast to our results, a marked reduction of STN activity was reported to be associated with the onset of speech production in the only previous report of STN unit activity recorded during speech production (Watson and Montgomery, 2006), although that study was largely descriptive in nature, limiting comparisons to our data.…”
Section: Discussionsupporting
confidence: 65%
“…In both cases, significant time-frequency modulations emerged about 400 ms before spoken response onset and persisted throughout the execution of speech. Desynchronization of alpha and beta activity and synchronization of high frequency activity have been previously reported as markers of ongoing movement and movement-related patterns in the STN (Androulidakis et al, 2007;Kempf et al, 2007;Lipski et al, 2017;Geng et al, 2018;Lofredi et al, 2018). However, only modulation of beta activity during speech production has been reported (Hebb, Darvas, and Miller, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Both couplings showed a similar spatial topography: PAC and spike-phase locking were most pronounced near the superior border of the STN. Interestingly, one recent study also showed that the STN cell firings in PD patients were phase synchronized to both low-and highbeta-frequency cortical oscillations (59). Furthermore, this relationship was not exclusive to motor cortex, as they show the STN firing also demonstrated phase synchronization to both premotor and sensory cortex.…”
Section: Neurosciencementioning
confidence: 97%